2018
DOI: 10.1038/s41419-018-1068-x
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-MEG3 inhibits activation of hepatic stellate cells through SMO protein and miR-212

Abstract: Activation of hepatic stellate cells (HSCs), a pivotal event in liver fibrosis, is considered as an epithelial–mesenchymal transition (EMT) process. Deregulation of long noncoding RNAs (lncRNAs) has been reported to be involved in a series of human diseases. LncRNA-maternally expressed gene 3 (MEG3) functions as a tumor suppressor in cancers and has been shown to play a vital role in EMT process. However, the biological role of MEG3 in liver fibrosis is largely unknown. In this study, MEG3 was reduced in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…MEG3 expression is decreased in fibrotic liver tissue and activated in primary HSCs. Overexpression of this lncRNA through a viral induction system also showed anti-fibrotic activity in murine CCl 4 -induced liver fibrosis [110,111]. In the immortalized human HSC line LX-2, MEG3 transcript levels are reduced in response to TGF-β treatment [111].…”
Section: Lncrnas In Liver Injury and Fibrosismentioning
confidence: 97%
“…MEG3 expression is decreased in fibrotic liver tissue and activated in primary HSCs. Overexpression of this lncRNA through a viral induction system also showed anti-fibrotic activity in murine CCl 4 -induced liver fibrosis [110,111]. In the immortalized human HSC line LX-2, MEG3 transcript levels are reduced in response to TGF-β treatment [111].…”
Section: Lncrnas In Liver Injury and Fibrosismentioning
confidence: 97%
“…MEG3 overexpression and its interaction with smoothened (SMO) participated in the suppression of epithelial to mesenchymal transition (EMT). On the other hand, miR-212 regulated the Hh pathway to mediate the effects of MEG3 on the EMT process [49]. These results suggest that MEG3 may play an important role in liver fibrosis progression and stellate cell activation and may serve as a novel potential diagnostic biomarker and therapeutic target for liver fibrosis.…”
Section: Meg3mentioning
confidence: 88%
“…Chen et al reported that MEG3 serum levels are low in chronic hepatitis B (CHB) patients and negatively correlate with the degree of liver fibrosis [47]. In addition, MEG3 has other mechanisms of inhibiting HSC activation [49]. MEG3 overexpression and its interaction with smoothened (SMO) participated in the suppression of epithelial to mesenchymal transition (EMT).…”
Section: Meg3mentioning
confidence: 99%
“…LncRNAs induced by HCV infection may regulate the expression of coding genes required for the replication of the virus or regulation of genes involved in the cellular antiviral response 33 . The expression levels of the lncRNA maternally expressed gene 3 (MEG3) 34 and the lincRNA p21 35 have been found to be reduced during liver fibrosis and, thus, may potentially serve as biomarkers of fibrosis. The lncRNA growth arrest-specific transcript 5 (GAS5) inhibits HCV replication 36 and participates in the activation and proliferation of HSCs 37 .…”
Section: Discussionmentioning
confidence: 99%